Efectividad de la benzocaina en gel al 20% y la lidocaina en solución al 10% en pacientes que requieren punción en la mucosa oral. Un ensayo clínico controlado aleatorizado cruzado a triple ciego - Arbildo Vega, Heber Isac (2015)
ABSTRACT: The objective of this study was to determine the effectiveness of benzocaine 20% gel and lidocaine in 10% solution in patients requiring puncture in the oral mucosa. This is a randomized controlled clinical trial to triple-blind, cross-over design. It was held at the dental clinic of the Unit of Second Specialization in Dentistry (usee) of the National University of Trujillo, in the months of November and December 2010 and January to March 2011. The sample consisted of 60 patients, each patient signed an informed consent and underwent a review of their status by anxiety scale state-trait anxiety (STAI). Before the puncture in the oral mucosa four preparations (2 topical anesthetics and 2 placebo) and then determine and compare the effectiveness of preparations in reducing pain using a visual analogue scale (VAS) was applied. For data collection a special token was used for that purpose. For comparison of the effectiveness of preparations Analysis of Variance (ANOVA). The effectiveness of the gel and anesthetic solution was evaluated using Tukey's test for multiple comparisons and students T. Statistical significance was 5%. We found that benzocaine 20% gel and lidocaine in 10% solution are effective at reducing pain at the puncture and that there is no statistically significant relationship (p= 0.0575) between the effectiveness of each. The administration of benzocaine 20% gel or lidocaine in 10% solution to reduce pain puncture equal and can be used interchangeably in everyday dental practice.